LEARNING AGILITY AND INNOVATIVE BEHAVIOR: THE ROLES OF LEARNING GOAL ORIENTATION AND LEARNING ORGANIZATION - Putri, Yashinta; Suharti, Lieli (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Today's dynamic changes in the external environment require the company to make adjustments in order to survive. Employees must also be more innovative and competent to support the competitiveness of the organization. This study aims to examine the effect of learning organization and learning goal orientation on learning agility and their impact on innovative behavior. The type of research used in this research is explanatory with a quantitative approach. The research population is Generation Y employees who work in the banking sector in Central Java. The sampling technique used is judgmental sampling with the number of respondents being targeted at 145 people. However, in distributing questionnaires using goggle form, in 1 month of research, only 105 respondents could be analyzed further. The analysis technique uses Structural Equation modeling with PLS software. The results of the study found that learning goal orientation and learning organization had a positive effect on learning agility. Furthermore, learning agility was also found to have a positive effect on innovative behavior. Additional findings found that learning goal orientation and learning organization also have a direct positive effect on innovative behavior, although the effect tends to be weak Keywords: learning agility, innovative behavior, learning goal orientation, learning organization